Persepsi Perempuan Di Jemaat Namaasi Meselesek Tentang Perceraian Akibat Kekerasan Dalam Rumah Tangga - Mea, Friska; Mosooli, Ermin Alperiana; Pohan, Juan Erwin (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2023)
Until now, the Church still prohibits divorce among its congregation. However, the fact is that the divorce rate continues to rise. One of the causes of divorce in Indonesia is domestic violence (KDRT), where the victims are mostly women. This research aims to determine the perceptions of Christian women in one of the local churches in Central Sulawesi regarding divorce due to domestic violence. The research method used is quantitative with a survey approach. Data was taken using a questionnaire, measured using a Likert scale with the options of Strongly Agree, Agree, Disagree and Strongly Disagree. Data were analyzed using descriptive analysis using the SPSS application. Of the 30 respondents who participated, the results found that respondents gave an average response of Agree to the statements: 1) there is no point in maintaining a marriage full of violence; 2) divorce is one way to end domestic violence; 3) divorce is the victim's courage to end domestic violence behavior; 4) the church's prohibition on divorce is one of the obstacles for victims to escape the shackles of domestic violence. From these results, it can be concluded that if, in dealing with the problem of domestic violence, the church only insists on prohibiting its citizens from divorcing without providing concrete solutions for victims of domestic violence, then the divorce ban will not be effective in reducing the rate of increase in the divorce rate among Christians.